Analisis Pengaruh Proporsi Hutang, EPS Dan Oversubscription Terhadap Fenomena Underpricing: Studi Pada Perusahaan IPO (Initial public offering) 2017- 2020 - Aisy Haniifah; Nani Hartati (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sunan Ampel Surabaya, 2021)
The purpose of this study was to examine the effect of the proportion of debt, EPS, and oversubscription on the underpricing phenomenon in IPO’ s on the Indonesia Stock Exchange 2017-2020. Sampling in this study was carried out using purposive sampling method, namely the sampling technique with certain considerations. To test the hypothesis, this study uses secondary data obtained by means of observational studies, literature studies and internet research, and processed using eviews 10. The results of this study indicate that the proportion of debt has no significant effect on underpricing . Earning per share was found to have a significant positive effect on underpricing . Oversubscription was also found to have a significant positive effect on underpricing .